Employment and taxes in Latin America: An empirical study of the effects of payroll, corporate income and value-added taxes on labor outcomes (2016)
This paper empirically explores the effects of payroll taxes, value-added taxes and corporate income taxes on a variety of labor market outcomes such as participation, employment, informality, and wages. The results are based on national-level data of labor variables for 15 Latin American countries, and indicate that the effects of each tax are markedly different and may depend on several aspects of labor and tax institutions. Payroll taxes reduce employment and increase labor costs when their benefits are not valued by workers, but otherwise may increase labor participation and not raise labor costs. Value-added taxes increase informality and reduce skilled labor demand. In contrast, corporate income taxes may help reduce informality, especially among low education workers, but when tax enforcement capabilities are strong they may reduce labor participation and employment of medium- and high-education workers